Annexin A2 mediates secretion of collagen VI, pulmonary elasticity and apoptosis of bronchial epithelial cells - Dassah, MaryAnn (The Company of Biologists, 2014)
The annexins are an evolutionarily conserved family of phospholipid-binding proteins of largely unknown function. We observed that the AnxA2(−/−) lung basement membrane specifically lacks collagen VI (COL6), and postulated that ANXA2 directs bronchial epithelial cell secretion of COL6, an unusually large multimeric protein. COL6 serves to anchor cells to basement membranes and, unlike other collagens, undergoes multimerization prior to secretion. Here, we show that AnxA2(−/−) mice have reduced exercise tolerance with impaired lung tissue elasticity, which was phenocopied in Col6a1(−/−) mice. In vitro, AnxA2(−/−) fibroblasts retained COL6 within intracellular vesicles and adhered poorly to their matrix unless ANXA2 expression was restored. In vivo, AnxA2(−/−) bronchial epithelial cells underwent apoptosis and disadhesion. Immunoprecipitation and immunoelectron microscopy revealed that ANXA2 associates with COL6 and the SNARE proteins SNAP-23 and VAMP2 at secretory vesicle membranes of bronchial epithelial cells, and that absence of ANXA2 leads to retention of COL6 in a late-Golgi, VAMP2-positive compartment. These results define a new role for ANXA2 in the COL6 secretion pathway, and further show that this pathway establishes cell–matrix interactions that underlie normal pulmonary function and epithelial cell survival.